Does long-term cultivation of saplings under elevated CO2 concentration influence their photosynthetic response to temperature? - Šigut, Ladislav; Holišová, Petra; Klem, Karel; Šprtová, Mirka; Calfapietra, Carlo; Marek, Michal V; Špunda, Vladimír; Urban, Otmar (Annals of botany, 2015)
BACKGROUND AND AIMS: Plants growing under elevated atmospheric CO2 concentrations often have reduced stomatal conductance and subsequently increased leaf temperature. This study therefore tested the hypothesis that under long-term elevated CO2 the temperature optima of photosynthetic processes will shift towards higher temperatures and the thermostability of the photosynthetic apparatus will increase. METHODS: The hypothesis was tested for saplings of broadleaved Fagus sylvatica and coniferous Picea abies exposed for 4-5 years to either ambient (AC; 385 µmol mol(-1)) or elevated (EC; 700 µmol mol(-1)) CO2 concentrations. Temperature response curves of photosynthetic processes were determined by gas-exchange and chlorophyll fluorescence techniques. KEY RESULTS: Initial assumptions of reduced light-saturated stomatal conductance and increased leaf temperatures for EC plants were confirmed. Temperature response curves revealed stimulation of light-saturated rates of CO2 assimilation (Amax) and a decline in photorespiration (RL) as a result of EC within a wide temperature range. However, these effects were negligible or reduced at low and high temperatures. Higher temperature optima (Topt) of Amax, Rubisco carboxylation rates (VCmax) and RL were found for EC saplings compared with AC saplings. However, the shifts in Topt of Amax were instantaneous, and disappeared when measured at identical CO2 concentrations. Higher values of Topt at elevated CO2 were attributed particularly to reduced photorespiration and prevailing limitation of photosynthesis by ribulose-1,5-bisphosphate (RuBP) regeneration. Temperature response curves of fluorescence parameters suggested a negligible effect of EC on enhancement of thermostability of photosystem II photochemistry. CONCLUSIONS: Elevated CO2 instantaneously increases temperature optima of Amax due to reduced photorespiration and limitation of photosynthesis by RuBP regeneration. However, this increase disappears when plants are exposed to identical CO2 concentrations. In addition, increased heat-stress tolerance of primary photochemistry in plants grown at elevated CO2 is unlikely. The hypothesis that long-term cultivation at elevated CO2 leads to acclimation of photosynthesis to higher temperatures is therefore rejected. Nevertheless, incorporating acclimation mechanisms into models simulating carbon flux between the atmosphere and vegetation is necessary.
Keywords: Photosynthesis; Chlorophyll; Plant Leaves; Photosystem II Protein Complex; aklimatizace; European beech; Picea; Fagus sylvatica; CO2 assimilation; světlo; Temperature; semenáček; elevated CO2 acclimation; teplota; ribulosafosfáty; thermotolerance; Acclimatization; chlorofyl; Ribulose-Bisphosphate Carboxylase; listy rostlin; Light; Rubisco carboxylation; photorespiration; photosystem II photochemistry; fotosystém II (proteinový komplex); ribulosa-1,5-bisfosfát-karboxylasa; Carbon Dioxide; Seedlings; Picea abies; oxid uhličitý; Climate change; smrk; Norway spruce; fotosyntéza; Ribulosephosphates